2011
DOI: 10.1002/pc.21153
|View full text |Cite
|
Sign up to set email alerts
|

Morphological characterization and electrochemical/electrical properties of poly(N‐vinyl carbazole)/montmorillonite composites

Abstract: A series of poly(N‐vinyl carbazole) (PNVCz)/sodium montmorillonite (Na+MMT) and PNVCz/organo‐MMT composite materials have been successfully prepared by in situ free radical polymerization with cerium ammonium nitrate (CAN) as initiator in the presence of inorganic nanolayers of hydrophilic Na+MMT or organophilic organo‐MMTs, modified with octadecylamine (ODA) and trimethyl stearyl ammonium (TMSA). The synthesized materials were subsequently characterized by Fourier transform infrared spectroscopy (FTIR), X‐ray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…In our another paper, we investigated the effect of intercalation agent and mixing method on the morphologic, thermal and electrochemical properties of PNVCz‐based composite materials prepared by in situ free radical polymerization in the presence of CAN and two‐dimensional MMT layers as initiator and inorganic component, respectively, and observed that the improvement intermolecular interactions, the widened interlayer distances and more homogeneous morphologies were obtained with PNVCz/ODA (octadecyl amine)—MMT composites, when ODA as intercalating agent and sonication with high‐power sonic tip as mixing method were used for modification and dispersion of silicate layers, respectively. Furthermore, the conductivity of PNVCz/MMT composite composed of nonconductive form of PNVCz chains and organophilic ODA‐MMT particles increased from 10 −15 to 10 −5 S cm −1 .…”
Section: Introductionmentioning
confidence: 98%
“…In our another paper, we investigated the effect of intercalation agent and mixing method on the morphologic, thermal and electrochemical properties of PNVCz‐based composite materials prepared by in situ free radical polymerization in the presence of CAN and two‐dimensional MMT layers as initiator and inorganic component, respectively, and observed that the improvement intermolecular interactions, the widened interlayer distances and more homogeneous morphologies were obtained with PNVCz/ODA (octadecyl amine)—MMT composites, when ODA as intercalating agent and sonication with high‐power sonic tip as mixing method were used for modification and dispersion of silicate layers, respectively. Furthermore, the conductivity of PNVCz/MMT composite composed of nonconductive form of PNVCz chains and organophilic ODA‐MMT particles increased from 10 −15 to 10 −5 S cm −1 .…”
Section: Introductionmentioning
confidence: 98%
“…The discovery of polymer nanocomposites, in which at least one dimension of the reinforcement phase is less than 100 nm, has resulted in a tremendous research effort to generate functional materials by synergistically combining the properties of constituent materials (Alexandre and Dubois, 2000;Okada et al, 1995;Giannelis, 1996;LeBaron et al, 1999;Brechet et al, 2001;Pavlidoua and Papaspyrides, 2008;Mark, 1996). The incorporation of fillers such as layered silicates into the polymer materials to generate composites has been done already for half a century.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the early 1990s, Toyota studied polyamide nanocomposites; Toyota's researchers dispersed electrostatically held 1-nm thick layers of the layered alumino-silicates in the polymer matrix on a nanometer level. Since then, substantial improvements in properties including strength, modulus, thermal stability, flame retardancy, and a decrease in gas permeability at very low filler contents as compared to the conventional composites (Lan et al, 1994;Chin et al, 2001;Lim et al, 2002;Wang and Pinnavaia, 1998;Messersmith and Giannelis, 1995;Yano et al, 1997;Shi et al, 1996;Giannelis, 1996;LeBaron et al, 1999;Mittal, 2007a;Osman et al, 2007) have been reported. The route suggested by the Toyota researchers was an in situ generation of polymer nanocomposites by polymerizing monomers in the presence of the silicates.…”
Section: Introductionmentioning
confidence: 99%